Comparative Study on Methotrexate alone Versus Combination Therapy with Methotrexate Plus Chloroquine Plus Low Dose Prednisolone in the Treatment of Rheumatoid Arthritis (Medicine Today, 2017)
Rheumatoid Arthritis (RA) has significant contributor to the global burden of disease and affects people in all communities across the world. It is a chronic inflammatory disease of the locomotors system that leads to substantial disability, loss of productivity and increased mortality. The Study was conducted among the RA patients based on broad objective of exploring the efficacy and adverse effects of triple combination therapy. This was an open, randomized, prospective study which followed qualitative research method. A total 61 patients were included in the trail. All subjects were randomly selected to combination therapy and MTX group. One patient from each group stopped the drugs due to adverse effects. Finally 59 patients completed the trail. 33 belonged to combination therapy group and 26 to MTX. Combination therapy is the best and easiest than others modifying anti-rheumatic drug used. Combination therapy with Methotrexate, Chloroquine and low dose Prednisolone is better than Methotrexate alone.Medicine Today 2017 Vol.29(2): 26-29